Smart City Status in Branding of the “Following Cities” from the 2022 Global Smart Cities Ranking - Szymon Ostrowski (Polish Political Science Yearbook)
The paper’s main objective is to analyze what a smart city is according to The United Nations Public Administration Network and to describe the potential relation between the smart city status of “following cities” of UNPAN’s 2022 Global Smart Cities Ranking and their branding and image. New technologies are a significant part of the development of modern cities, and they should not be overlooked, even in a matter of the image of cities. Researched cities are Mumbai, Rio de Janeiro, Buenos Aires, and Cairo, which are among the top 20 smart cities according to UNPAN. Still, they are not considered cities that enjoy the repute of advanced, thus called “following cites”. The paper also analyzes the cities’ current branding policies and politics concerning modern technologies and advancement. Even if impressive, the digitization of life in “following cities” is not well-developed compared to other smart cities due to a lack of resources and the will of cities to change their branding and digitization strategies.